Mixed Fibrinolytic Phenotypes in Decompensated Cirrhosis and Acute‐on‐Chronic Liver Failure with Hypofibrinolysis in Those With Complications and Poor Survival. Issue 4 (24th October 2019) - Blasi, Annabel; Patel, Vishal C.; Adelmeijer, Jelle; Azarian, Sarah; Hernandez Tejero, Maria; Calvo, Andrea; Fernández, Javier; Bernal, William; Lisman, Ton
Abstract : Background and Aims: Patients with liver disease acquire complex changes in their hemostatic system, which results in a fragile rebalanced status. The status of the fibrinolytic system is controversial, as is the role of fibrinolytic dysfunction in bleeding and thrombosis in patients with cirrhosis. Here, we aimed to determine fibrinolytic status and its relationship with outcome in acutely ill patients with cirrhosis. Approach and Results: We assessed plasma fibrinolytic potential in a large cohort of patients with acutely decompensated cirrhosis (AD, n = 52) or acute‐on‐chronic liver failure (ACLF, n = 57). Compared with 40 healthy volunteers, median clot lysis times (CLTs) were shorter in patients with AD but comparable to controls in patients with ACLF. However, the variability in CLTs in patients was much larger than in healthy controls, and in both patient groups, a proportion of patients had clearly prolonged or shortened CLTs. The variability in CLTs in patients was not readily explained by variations in plasma levels of key fibrinolytic proteins. However, CLTs were clearly related to clinical characteristics, with longer CLTs in patients with sepsis and patients with any organ failure (as defined by the European Foundation for the Study of Chronic Liver Disease organ failure scores). CLTs were not different between patients that did or did not experience bleeding or a thrombotic event during follow‐up. Baseline CLTs were substantially longer in patients that died within 30 days of admission. Conclusions: Our study demonstrates a mixed fibrinolytic phenotype in acutely ill patients with cirrhosis with baseline hypofibrinolysis associated with sepsis, organ failure, and short‐term mortality. These associations may be explained by defective clearance of intraorgan microthrombi that have been proposed to drive organ failure.